Role of Yoga during Third trimester - Patel, Namita (International Research Journal of Ayurveda & Yoga, 2021)
One of the most miraculous bodily processes is pregnancy. Pregnancy, which is commonly described as the gestation of offspring within a female’s body, has a number of biological components that enable this process to be completed successfully. Fertilization, antenatal stage, intra-natal period, postnatal period, and inter conceptional period are the five stages of the maternity cycle. Although a beautiful process, pregnancy is a dangerous condition and numerous complications can occur that affect both the fetus and the person carrying the fetus during and after pregnancy. Pregnancy and childbirth complications are the leading cause of death and disability among women in developing countries, according to the World Health Organization. Ayurveda is the best method for combating the problems and illnesses that threaten our planet because of its personalized approach to pregnancy. Yoga is used to treat a wide range of immunological, neuromuscular, psychological, and pain-related issues. It appears to be successful in enhancing pregnancy, labor, and birth outcomes, according to recent reports.